You Only Live Once! Understanding Indonesian and Taiwan Travel Intention During COVID-19 Pandemic - Akhrani, Lusy Asa; Cheng, Wen; Herani, Ika; Riani, Yuyun Agus; Pratiwi, Resti Diah; Fahmi, Aqsha Ade; Ammaritza, Aubrey; Barlamana, M. Haikal Azaim (Frontiers in Psychology, 2022)
Indonesia and Taiwan are two countries that have been affected by the tourism sector, although with different policies to control the COVID-19 pandemic. Taiwan is known as a country with pandemic policies that have been recognized around the world, although it has a high vulnerability to experiencing a high number of infections due to its geographical and political position close to the source of the pandemic. On the other hand, Indonesia is known for its controversial pandemic management and control policies. Indonesia and Taiwan have carried out various public policies to increase tourism activities during the pandemic, such as accelerating vaccination in tourist areas and for tourists, as well as various other stimuli to stimulate tourism. The debate over vaccination raises questions about attitudes toward vaccines in society. The lack of clarity on psychosocial and political conditions creates confusion among the public in perceiving the COVID-19 pandemic and in perceiving the risks of traveling. This can affect people's attitudes toward vaccines, travel anxiety, and travel intentions. This study aims to analyze traveling intention due to the COVID-19 pandemic through COVID-19 Risk Perception, Fear of COVID-19, Risk Perception to Travel, Vaccine Attitude, and Fear to Travel. The research in Indonesia involved 358 respondents while the research in Taiwan involved 283 respondents. The research analysis used multiple regression and simple linear regression to ascertain the role of each association. The results showed that the travel intention of Indonesian tourists was formed from the direct and indirect roles of covid 19 risk perception, fear of covid 19, risk perception to travel, vaccine attitude, and fear to travel. Meanwhile, the travel intention of Taiwanese tourists is not influenced by a fear of covid. The travel intention model of Taiwanese tourists is formed from the direct and indirect roles of covid 19 risk perception, risk perception to travel, vaccine attitude, and fear to travel. This research contributes to tourism risk management in the face of pandemics, particularly in terms of government policies that can reduce tourism anxiety to travel during disasters.